All-optical packet switching for metropolitan area networks opportunities and challenges. - Yao, Shun (IEEE Communications magazine)
The fast evolution of networks has been continuously driven by new advances in enabling technologies, as well as the growth of Internet traffic. All-optical packet switching provides high throughput, rich routing functionalities, and excellent flexibility. These characteristics make it an excellent candidate for next-generation metropolitan area networks, which will be much more dynamic and demanding than today's networks. In this article we not only discuss some of the architectural challenges involved in the design of all-optical packet switched networks, but also present the reader a high-level picture of how such future networks could be integrated with other network segments, to provide users end-to-end connectivity with performance and simplicity